Long-Term Effect of Anti-Vegf Agents on Intraocular Pressure in Age-Related Macular Degeneration - Beato, João (2015)
Aim: To evaluate the effect of intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents on the development of sustained ocular hypertension (OHT) in patients with neovascular age-related macular degeneration (AMD). Methods: A retrospective study of patients with neo- vascular AMD who received unilateral intravitreal anti-VEGF treatment was performed. Fellow non-injected eyes were used as controls. Initial intraocular pressure (IOP) was measured before the first injection and final IOP was measured 3-4 weeks after the last injection. Eyes that re- quired IOP lowering treatment during follow-up were identified. Results: Seventy-two patients were eligible for the study. Sustained ocular hypertension (OHT) developed in 3 (4.2%) of the injected eyes and in 1 (1.4%) of controls. There was no statistically significant difference be- tween final IOP in the study and control groups. In the study group, patients who received >20 anti-VEGF injections showed a significantly larger variation of IOP during follow-up (p=0.034) Conclusion: Eyes receiving a higher number of injections suffer a significantly larger IOP varia- tion than eyes treated with fewer injections, but larger studies are needed to conclude if treatment with intravitreal anti-VEGF agents increases the risk of developing sustained OHT.